(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper represents all the aspects relating to the ratio analysis of Spice Jet and Jet Airways interpreted according to financial equation. This information for this report was gathered by searching and using secondary data such as financial statement. The important reason behind constructing an analysis is to abstract different information and data from financial statements either income statement or balance sheet, to predict the conclusions from those ratios and to simplify accounting data for investors. The present study is descriptive and analytical in nature.The 2017-2018 financial statements were collected from the official websites of the selected companies. The collected data can be tabulated and analyzed by using ratio analysis techniques.